Inspeksi Kualitas Hasil Las Proses Pengelasan SMAW dengan Menggunakan Jig Sebagai Alat Bantu - Dy, Rus Nal (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2021)
Shielded metal arc welding (SMAW) is one of the most widely used welding processes in various industries. It is also used in SMK and vocational school in college, as well as a topic of student final projects. While other welding processes produce a better weld than SMAW, it is still widely used because of its low production cost and a simple and portable welding machine. Eventhough, it is the simplest, in terms of equipment requirements, but it is, perhaps, the most difficult in terms of welder training and skill-level requirements. To overcome the problem, it would require a jig welding to be used by students to perform a welding process in order to conduct their final project without experienced welders’ help. In this study it has been designed and made a jig welding that is a design development out of an earlier jig welding that still has many weaknesses. The quality of the new jig welding is seen through a series of tests and inspections for the SMAW process’s results. Testing and inspection results show that a new jig welding overcome the weaknesses of the old one. The new jig was able to perform a welding process for position 1G for a 20 cm buttjoint with the use of electrode in a single welding process. The new jig also succeeded in reducing the vibrations that occur as the electrode moves during the welding process. The quality of the weld by using new jig was seen from the results of SMAW process conducted with the parameters of the process of variations in welding speed (1.8 mm/s, 2.8 mm/s and 3.8 mm/s) and current usage (60 A and 70 A). Visual inspection shows that the use of a new jig welding could eliminate the number and type of welding defects. And from dimensional inspection of welds, it shows that a new jig welding has been able to generate a standardized measure of welds, especially when doing a SMAW process for buttjoint with a 2-mm root gap.